2014
DOI: 10.3201/eid2011.140915
|View full text |Cite
|
Sign up to set email alerts
|

Raw Pig Blood Consumption and Potential Risk forStreptococcus suisInfection, Vietnam

Abstract: We assessed consumption of raw pig blood, which is a risk factor for Streptococcus suis infection in Vietnam, by using a mix-method design. Factors associated with consumption included rural residency, age, sex, occupation, income, and marital status. We identified risk groups and practices and perceptions that should be targeted by communication programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 15 publications
2
29
0
Order By: Relevance
“…These infections afflict persons in close contact with infected pigs or pork-derived products ( 4 , 5 ). Although sporadic cases of S. suis infections in humans had been reported worldwide previously, in the summer of 2005, China recorded the largest and most highly diffused outbreak of S. suis infection in humans, with 215 cases reported and 39 deaths ( 6 , 7 ).…”
mentioning
confidence: 99%
“…These infections afflict persons in close contact with infected pigs or pork-derived products ( 4 , 5 ). Although sporadic cases of S. suis infections in humans had been reported worldwide previously, in the summer of 2005, China recorded the largest and most highly diffused outbreak of S. suis infection in humans, with 215 cases reported and 39 deaths ( 6 , 7 ).…”
mentioning
confidence: 99%
“…A great proportion of humans infected by S. suis serotype 2 were found to be associated with the habit of farming domestic animals at home, in which pigs are raised in closed small piggeries with unhygienic conditions and are slaughtered without being quarantined, which results in contamination of raw pork products [15,16,17]. Moreover, the unsafe habit of purchasing pork in flea markets and the consumption of undercooked animal products are well-established risk factors for acquiring many infectious diseases, especially S. suis serotype 2 from pigs [6,8]. A recent study from Hong Kong reported heavy contamination of raw pork meat at local supermarkets or wet markets with S. suis; therefore, hot and humid climates may facilitate the growth of S. suis in raw pork products [3].…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus suis (S. suis) is a Gram-positive bacterium and, with clinical relevance in pigs, is emerging in humans [8,9]. Based on differences in antigenic properties of the polysaccharide capsule, 35 S. suis serotypes have been distinguished to date, of which serotype 2 is most commonly associated with disease in humans and pigs worldwide [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Farms were selected based on census data and randomised from three different scales of production (small, medium, large). The rationale for the animal enterics survey was to review animal census data for the province; to Streptococcus suis, a pig bacterium that can cause bacterial meningitis in humans (Huong et al 2014;Wertheim et al 2009). …”
Section: Implementation Differences Between Dong Thap and Bavi Sitesmentioning
confidence: 99%
“…Several interface studies have included extensive qualitative interviews to assess attitudes, perceptions of risk and behavioural risk factors (Huong et al 2014;Liao et al 2014;Manabe et al 2012;Paul et al 2013), but the focus has consistently been on implications for human health rather than on animal impact. The community cohort project described here is part of the Vietnam Initiative on Zoonotic Infections (VIZIONS) program, which encompasses both hospital-based syndromic surveillance and community-based research on zoonotic pathogens.…”
mentioning
confidence: 99%